Why Catholic Theology Needs Metapshysics: A Christological Perspective - White, Thomas Joseph (Teologia w Polsce, 2020)
The Chalcedonian confession of faith asserts that Christ is one person, the Son of God, subsisting in two natures, divine and human. The doctrine of the communication of idioms is essential to the life and practices of the Church insofar as we affirm there to be properties of deity and humanity present in the one subject, the Word made flesh. Such affirmations are made without a confusion of the two natures or their mutually distinct attributes. The affirmation that there is a divine and human nature in Christ is possible, however, only if it is also possible for human beings to think coherently about the divine nature, analogically, and human nature, univocally. Otherwise it is not feasible to receive understanding of the divine nature of Christ into the human intellect intrinsically and the revelation must remain wholly alien to natural human thought, even under the presumption that such understanding originates in grace. Likewise we can only think coherently of the eternal Son’s solidarity with us in human nature if we can conceive of a common human nature present in all human individuals. Consequently, it is only possible for the Church to confess some form of Chalcedonian doctrine if there is also a perennial metaphysical philosophy capable of thinking coherently about the divine and human natures from within the ambit of natural human reason. This also implies that the Church maintains a “metaphysical apostolate” in her public teaching, in her philosophical traditions, as well as in her scriptural and doctrinal enunciations.